Restoration of the Bishop Danilo's mausoleum at Eagle's Rock, Cetinje (Montenegro) - Svetislav G. Popović; Dragutin Đuričić; Svetlana K. Perović (Tehnički Vjesnik, 2017)
The case study refers to the restoration of the Bishop Danilo's mausoleum at Eagle’s Rock, in Cetinje Royal Capital of Montenegro. This is one of the most significant unmovable cultural heritage monuments in Cetinje's historic center. Presentation of the project for the restoration of the mausoleum and the process of construction works indicated the specificity and sensitivity of the restoration and conservation of cultural monuments that carry significant messages from the history of the people and are a part of collective memory. During the last three decades, the mausoleum was repaired twice. The first structural sanation was done in 1985, eliminating consequences of the earthquake of 1979, and the other one was done on the initiation of the Republic Institute for Protection of Cultural Monuments in Cetinje, following an investigation of the existing state of the mausoleum’s structure, which was conducted in 2004. This paper presents the character of defects that occurred over time and were found during the investigation of the structure of the object, the causes of defect occurrence, conservation requirements for the restoration, choice of the most rational solution in 2007, method for construction works on the object, as well as the review of the object after the completion of the restoration in 2011. Research results point out the complexity of the restoration of objects that have special cultural value, regardless of the dimensions and complexity of the architectural structure itself.